Antioxidant Assay of Endophytic Fungi Extract from Mango Mistletoe (Dendrophthoe pentandra (L.) Miq) Leaves - Dewi Qurrot 'Aini; Nour Athiroh Abdoes Sjakoer; Nurul Jadid Mubarakati (JSMARTech: Journal of Smart Bioprospecting and Technology, 2023)
Endophytic fungi found in mango mistletoe (Dendrophthoe pentandra (L.) Miq) leaves may potentially create a variety of bioactive antioxidant compounds, and their prospects for large-scale production especially for phytopharmaceuticals products without excessive natural exploitation. The objective of this study was to investigate the antioxidant properties of endophytic fungal extracts obtained from mango mistletoe leaves. The method used is experimental laboratory research with a quantitative approach through the DPPH (2,2-diphenyl-1-picrylhydrazyl) free radical scavenging activity method. The test sample concentrations ranged from 120 µg/ml to 200 µg/ml. The results of this study indicated that isolates of EFMM 1 (Aspergillus spp.) has an IC50 of -12,27 µg/ml, EFMM 2 (Neurospora spp.) has an IC50 of 10,40 µg/ml, EFMM 3 (Hormiscium spp.) has an IC50 of 49,44 µg/ml, and EFMM 4 (Exserohillum spp.) has an IC50 of 299,32 µg/ml. The conclusion is that EFMM 1 doesn’t have an antioxidant activity, while EFMM 2 has the highest antioxidant potential comparable to ascorbic acid.